2013
DOI: 10.1177/1358863x13475836
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related variation in the clinical presentation and outcomes of critical limb ischemia

Abstract: Critical limb ischemia (CLI) is a major cause of limb loss and mortality among patients with advanced peripheral artery disease. Our objective was to evaluate the gender-specific differences in patient characteristics and clinical outcomes among patients with CLI. We performed a retrospective analysis of 97 women and 122 men presenting with CLI who underwent angiography from 2006 to 2010. Baseline demographics, procedural details, and lesion characteristics were assessed for each patient. Kaplan–Meier analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 27 publications
2
49
1
Order By: Relevance
“…In a small cohort of 97 women and 122 men with PAD, McCoach et al found no difference in limb-specific outcomes, but women had more major adverse cardiovascular events after procedures to improve blood flow and to prevent amputation. 24 Using large state databases to evaluate outcomes for patients with PAD, Egorova et al showed statistically significant differences in mortality after treatment for PAD between women (4.95%) and men (4.37%) during a 6-year period. 25 In the work presented here, women had better amputation-free survival ranging from 10% to 28% across all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort of 97 women and 122 men with PAD, McCoach et al found no difference in limb-specific outcomes, but women had more major adverse cardiovascular events after procedures to improve blood flow and to prevent amputation. 24 Using large state databases to evaluate outcomes for patients with PAD, Egorova et al showed statistically significant differences in mortality after treatment for PAD between women (4.95%) and men (4.37%) during a 6-year period. 25 In the work presented here, women had better amputation-free survival ranging from 10% to 28% across all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This registry comprises all patients with a clinical diagnosis of PAD who underwent diagnostic angiography or therapeutic endovascular intervention, or both, at the UC Davis Medical Center between June 2006 and May 2013, as previously described. 16 At the time of data extraction, the registry included 1201 patients who underwent 1897 procedures. A total of 753 patients presented with claudication or CLI and were included in this study; the other patients in the registry included those presenting with acute limb ischemia, carotid artery stenosis, subclavian artery stenosis, or renal artery stenosis.…”
Section: Methodsmentioning
confidence: 99%
“…17 The study protocol was approved by the Institutional Review Board at the University of California, Davis Medical Center. All patients in the registry with CLI (N=464) were analyzed.…”
Section: Methodsmentioning
confidence: 99%